Ultrasonic extraction of palm pressed fibre for oil recovery - Azyyati, Abd Hamid (2015)
Palm pressed fiber (PPF) is the solid waste produced from palm oil milling company after the pressing process. Recovery of oil and reuse of the palm pressed fiber is a great opportunity for cost saving in the oil processing industry. The objective of the research is to recover residual oil which still left in the PPF by using ultrasonic-assisted extraction method (UAE). The process is carried out by priory drying process of the PPF at 60 °C for 1 hour. Then the dried sample will undergo the extraction process in the ultrasonic bath by using methanol as a solvent. The effect of solid: liquid ratio and extraction time are varies in the range of (1:3-1:8) and (0 minutes-60 minutes) respectively. Yield of the extracted oil are measured for all conditions. Results from studies shows that the highest yield is 12.90% which obtained at the condition 1:5 (g/ml) of the solid: liquid ratio and 30 minutes of the extraction time. Hence, the result from Gas chromatography–mass spectrometry (GC-MS) has confirmed that the properties of the extracted oil are almost similar to the crude palm oil (CPO).